Development strategy and sustainability of credit loans of the banking sector in Serbia - Ivančević Jovana; Milošević Snežana; Radović Milan (Anali Ekonomskog fakulteta u Subotici, 2015)
The rapid growth in credit activities of banks in Serbia dates from 2003. Using a big difference in interest rates in the market of Serbia and the EU member states, foreign banks were key leaders of rapid growth. Soon, the expansion of credit activity led to a reduction in interest rates and the increase in the level of indebtedness of the private sector. The risks of accelerated growth from the first were not visible, but escalated later as a result of underestimation of credit risk. The consequences are visible years later, because the problems with the repayment of the loans taken as a rule occur in the later stages of repayment. Those changes were reflected in the growth of the share of non-performing loans in total loans. The growing risk aversion, sharpening of credit standards, reducing the external financing sources, were just some of many factors that have had led to intensified competition in local markets. This paper attempted to analyze the structure of competition and concentration in the Serbian market. The average rate of growth indicators depth of the banking sector is examined as well as measured by the ratio of the total amount of loans to GDP and the ratio of total loans and NPL.